157 Stent Encrustation and Indwelling Stent Times. (19th August 2022) - Debo-Aina, A; Datta, S; Rix, G; Keoghane, S; Maan, Z
Abstract: Introduction: A pathways streamlining stone management identified four rate-limiting processes causing delay and affecting outcome. Key performance indicators (KPI) with set targets were created to address them. These are: Time to CT with report (< 24hrs). Time to operative care (< 48hrs). Time to discussion at stone MDT ≤2 weeks. Indwelling stent time (IDST) ≤12 weeks Ureteric-stents cause morbidity if left in-situ long-term. This includes bacterial colonization and encrustation. Methods: Aim: a) identify IDST during pre-COVID and COVID periods, b) review encrusted-stents removed within the study timeframe and c) root-cause for delayed stent removal and encrustation. Stent register reviewed between Jan-2019 and Mar-2021. Mean IDST pre- and post-COVID calculated. Information on indication, insertion date and removal retrieved from register and clinical-notes. Root-cause analysis to identify factors influencing delayed removal and encrustation. Results: 841 stents inserted within study timeline; 436 pre-COVID and 405 during COVID. Identical stent-times for both periods, 86% cases pre-COVID and 85% during COVID having IDST <12 weeks. Average IDST of 6 weeks and 5 weeks in pre-COVID and COVID periods respectively. 11 encrusted-stents removed (7 pre-COVID, and 4 COVID), with average encrusted-stent duration of 29 weeks pre-COVID and 16 weeks during COVID. Factors involved in encrustation and delayed removal include systems and patient-related factors, failed initial removal, complex surgical planning, ESWL and dissolution therapy. Discussion & Conclusions: No difference in IDST during pre-COVID and COVID periods. A lowered encrusted IDST during COVID, likely attributed to departmental prioritisation of stone-pathway, stent register, and use of a green-listed operative site.